2018
DOI: 10.1016/j.lindif.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

School effects on students' engagement with school: Academic performance moderates the effect of school support for learning on students' engagement

Abstract: School effects on students' engagement with school: academic performance moderates the effect of school support for learning on students' engagement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 52 publications
0
27
0
5
Order By: Relevance
“…We controlled for student prior academic performance, age, and gender (0 = male; 1 = female) in our analyses because these factors are shown to influence student engagement (Lietaert, Roorda, Laevers, Verschueren, & De Fraine, 2015; Moreira et al, 2018; Wang & Eccles, 2012b). We considered students’ academic performances in standardized national examinations to be a proxy for academic ability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We controlled for student prior academic performance, age, and gender (0 = male; 1 = female) in our analyses because these factors are shown to influence student engagement (Lietaert, Roorda, Laevers, Verschueren, & De Fraine, 2015; Moreira et al, 2018; Wang & Eccles, 2012b). We considered students’ academic performances in standardized national examinations to be a proxy for academic ability.…”
Section: Methodsmentioning
confidence: 99%
“…The associations between student engagement and important academic outcomes such as academic performance and school completion are now well‐documented (Lee, 2014; Li & Lerner, 2011; Wang & Fredricks, 2014; Wang & Holcombe, 2010). Important developments have also been made to the current understanding of how engagement changes over time (Archambault & Dupéré, 2017; Zhen et al, 2019), and how this change is influenced by contextual factors (Moreira et al, 2018; Moreira & Lee, 2020; Wang & Eccles, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…This measure was designed for use with Portuguese adolescents but can be easily adapted for use in other countries. Recent studies have shown that student engagement in Portugal has similar dimensionality (Moreira & Dias, 2018) and characteristics to student engagement in other cultures (e.g., decreases with age; lower in students from lower socioeconomic status [SES] families; Moreira, Dias, et al, 2018). Having an instrument that captures the full multidimensional nature of the student engagement construct will have important implications for research on student disengagement and dropout, school interventions and policy, and the monitoring/assessment of engagement in students, including those for who the consequences of disengagement are more severe (e.g., students from disadvantaged backgrounds).…”
Section: Introductionmentioning
confidence: 99%
“…The reciprocal relationships between student engagement and academic performance have been studied extensively and are well established. Engagement predicts academic performance (Carbonaro, 2005; Lee, 2014), and academic performance also predicts student engagement (Chase et al, 2014; Moreira, Dias, et al, 2018; Wang & Eccles, 2012). It was also expected that student engagement would be associated with emotional well-being because at least one theory (Fredrickson, 2001) suggests that positive emotions broaden cognitions and behaviors and help build adaptive physical, intellectual, and social resources, such as engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found a strong connection between students' feeling of belonging and learning achievements [15]. For example, a supportive school climate and safe teacher-student relationships increase students' engagement [16,17]. Many studies state that students' sense of community and the satisfaction of their educational needs increase students' engagement with their studies [18].…”
Section: Introductionmentioning
confidence: 99%